Exponential Stability of laminated beam with constant delay feedback - Mpungu, Kassimu; Apalara, Tijani A. (Mathematical Modelling and Analysis, 2021)
In this article, we consider a system of laminated beams with an internal constant delay term in the transverse displacement. We prove that the dissipation through structural damping at the interface is strong enough to exponentially stabilize the system under suitable assumptions on delay feedback and coefficients of wave propagation speed.